Factors in the Sexual-Related Behaviour of Students in Makassar - Hamdani, Musyarrafah; ., Sabarinah; Krianto, Tri (KnE Life Sciences, 2018)
Data collected in Indonesia in 2012 showed that around 10% of adolescents aged 15-24 years had engaged in premarital sex, which could affect maternal health. However, since 2000, a school-based reproductive health programme has been implemented in Makassar, a large city in eastern Indonesia. This study, therefore, was aimed at describing factors associated with sexual-related behaviour in students in Makassar. The logistic regression analysis drew on data from 1823 respondents in Makassar who completed self-administered questionnaires as part of the 2011/2012 National Narcotics Board and Center for Health Research Universitas Indonesia survey. One fifth of the respondents reported engaging in sexual-related behaviour starting at a mean age of 15 years. The behaviour included lip kissing (18%), masturbation (6%), oral sex (5%), petting (4%), vaginal sex (3%) and anal sex (2%). Around 20% of the students smoked, while 8% consumed alcohol, and 1% used drugs. Smoking and alcohol affected the students’ sexual-related behaviour (OR 3, 95% CI 2–3; OR 2, 95% CI 1–3, respectively). Risk factors also included maternal characteristics, such as maternal orphan [.1] (OR 2, 95% CI 1–5) and working in the private sector (OR 2, 95% CI 1–2). School-based reproductive health programmes should pay significant attention to students’ smoking and alcohol-drinking behaviours and take into account the characteristics of students’ mothers. Throughout the paper, c [.1]larify whether maternal orphan refers to children without mothers or mothers who are orphans.